Effectiveness of Carbon Fibre Reinforced Polymer (CFRP) & Textile Reinforced Mortar (TRM) Strengthening on Circularised Non-Slender Reinforced Concrete Columns - Ochieng, Victor; Abuodha, Silvester; Mumenya, Siphila (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This research paper presents an experimental investigation into the effectiveness of Carbon fibre Reinforced Polymer (CFRP) and Textile Reinforced Mortar (TRM) for strengthening circularized non-slender reinforced concrete columns. The experiment examined the following parameters cross-section shape namely; - square, circular, and circularized, the strengthening material i.e. CFRP or TRM, and the number of wrapping layers of the strengthening material (one and two layers).  45 specimens were prepared, given various treatments, strengthened, and loaded uniaxially until failure.  The specimens were categorised into three series based on their cross-section geometry; - circular, square, and circularized. The results showed that the circular specimens recorded the highest axial capacity followed by the circularized specimens while the square specimens recorded the least axial capacity, CFRP confinement was more effective compared to TRM confinement in enhancing the axial capacity and ductility, and doubling the number of both CFRP and TRM layers from 1 to 2 resulted in a significant increase in both the axial capacity and ductility of the specimens. Consequently, the gain in axial capacity and the ductility of the strengthened specimens was sensitive to the number of wraps and the strengthening material. It was also noted that the failure modes of the specimens differed depending on the cross-section geometry. From the findings of this study, it is believed that circularisation and confinement using TRM & CFRP is a promising solution for retrofitting inadequate square columns.